The Application of Moon Orchid Corsage as a Decorative Element in Evening Gown - Shofia Ahdia; Mutiara Annandara (Corak, 2026)
This study is motivated by the need to develop three-dimensional ornaments in evening wear that not only emphasize aesthetics but also represent local cultural identity. Although Indonesian flora possesses strong visual potential, its application as a decorative source of inspiration in evening gown design remains relatively limited. Therefore, this research aims to create an evening gown inspired by the morphological characteristics of the Moon Orchid (Phalaenopsis amabilis) through the application of corsage techniques as three-dimensional decorative elements, as a form of three-dimensional interpretation of Indonesia’s national flower. The study employs a creative design methodology consisting of exploration, design development, and realization stages. The findings indicate that the petal structure of the Moon Orchid can be effectively transformed into layered corsages using satin and organza, resulting in a soft yet dramatic three-dimensional effect. The completed work successfully highlights feminine and elegant qualities while presenting the identity of local flora within the context of contemporary fashion design.